Temperature modelling of an homogeneous medium using genetically selected RBF (LIC) - Teixeira, C. A. (2013)
Temperature modelling of human tissue subjected to ultrasound for therapeutic use is essencial for an accurate instrumental assessment and calibration. In this paper punctual temperature modeling of a homogeneous medium, radiated by therapeutic ultrasound, is presented.